2013
DOI: 10.1016/j.autneu.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic transmission of baro- and chemoreceptors afferents in the NTS second order neurons

Abstract: Second order neurons in the nucleus tractus solitarius (NTS) process and integrate the afferent information from arterial baroreceptors with high fidelity and precise timing synaptic transmission. Since 2nd-order NTS neurons receiving baroreceptors inputs are relatively well characterized, their electrophysiological profile has been accepted as a general characteristic for all 2nd-order NTS neurons involved with the processing of different sensorial inputs. On the other hand, the synaptic properties of other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 60 publications
1
24
0
1
Order By: Relevance
“…There is well-documented evidence of direct excitatory projections from 2 nd order NTS peripheral chemoreceptive neurons to the RVLM (see Accorsi-Mendonca and Machado (2013) for review) which mediate sympathoexcitatory effect of peripheral chemoreceptor stimulation. Our model implies that there are at least two more indirect pathways mediated by the respiratory neurons ( Hypothesis 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is well-documented evidence of direct excitatory projections from 2 nd order NTS peripheral chemoreceptive neurons to the RVLM (see Accorsi-Mendonca and Machado (2013) for review) which mediate sympathoexcitatory effect of peripheral chemoreceptor stimulation. Our model implies that there are at least two more indirect pathways mediated by the respiratory neurons ( Hypothesis 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed that the NTS is a heterogeneous nucleus, which processes multimodal sensory afferents, including gustatory, nociceptive and enteric inputs (Hill et al, 1983; Rinaman et al, 1989; Du and Zhou, 1990), as well as heterogeneous multimodal input from the carotid body (Kumar and Prabhakar, 2011). Recently, we demonstrated that NTS neurons receiving direct projections from the carotid body present a large variability in the latency of evoked glutamatergic currents, suggesting an intrinsic heterogeneity of the sensory pathways from the carotid body to the NTS (Accorsi-Mendonça et al, 2011; Accorsi-Mendonça and Machado, 2013). …”
Section: Physiology Of the Peripheral Chemoreflex In Mammalsmentioning
confidence: 99%
“…In turn, the CVLM excites preganglionic parasympathetic neurons in the nucleus ambiguus (NA), which also receives excitatory input from the NTS, and projects (via the vagus nerve) to the heart to reduce the heart rate and stroke volume (62, 181). More importantly, the CVLM projects inhibitory (GABAergic) projections to the “vasomotor center” of cardiovascular system, the RVLM (59, 181, 183). The RVLM projects to and synapses on preganglionic sympathetic neurons located in the IMLCC of the spinal cord (59, 179, 182).…”
Section: The Baroreceptor Reflex In Healthy Pregnancy and Preeclampsiamentioning
confidence: 99%
“…The RVLM projects to and synapses on preganglionic sympathetic neurons located in the IMLCC of the spinal cord (59, 179, 182). Inhibition of the RVLM reduces the sympathetic tone to IMLCC, and it is this decrease in sympathetic nerve activity to the blood vessels, heart, and kidneys, that produces a corresponding decrease in mean arterial pressure (180, 181, 183). …”
Section: The Baroreceptor Reflex In Healthy Pregnancy and Preeclampsiamentioning
confidence: 99%